Analysis Of Iri And Sdi Methods As A Basis For Determining Road Functional Conditions - Octavia, Syarifah Nur; Yulistiyanti, Liana Dwi; Setyanta, Nunuk Chandra; Wicaksono, Reza Husain; Setyobudi, Risang (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2024)
Assessment  lof  lroad  lconditions  lneeds  lto  lbe  ldone  lperiodically  las  la  lreference  lin  ldetermining  levaluation  lof  lfunctional  lroad  lconditions.  lThe  lparameters  lrelated  lto  lfunctional  lconditions  lare  lthe  llevel  lof  lroughness,  las  lwell  las  lthe  lactual  llevel  lof  ldamage  lin  lthe  lfield  lsuch  las  larea,  lcrack  lwidth,  lnumber  lof  lholes  land  lthe  ldepth  lof  lthe  lgrooves  lof  lthe  lruts.  lBased  lon  lthe  lproblems  lmentioned  labove,  lit  lis  lnecessary  lto  lanalyze  lthe  lfunctional  lcondition  lof  lthe  lroad  lusing  lIRI  land  lSDI  lvalues  las  lwell  las  lthe  lcalculation  lof  lthe  lconstruction  lcost  lbudget  lon  lthe  lpakah  l-  lpucangan  l-  lgesikharjo  lroad  lsection.Setiawan,  lPradani  land  lMasoso  l(2019)  largued  lthat  l"assessment  lof  lroad  lsurface  lconditions  lis  lneeded  lto  ldetermine  lthe  lright  lroad  levaluation  lprogram,  lone  lof  lthe  lparameters  lused  lis  lthe  lInternational  lRoughness  lIndex  l(IRI)  land  lSurface  lDistress  lIndex  l(SDI).  lThe  lresults  lof  lthis  lstudy  lare  lthe  lPakah  l-  lPucangan  l-  lGesikharjo  lroad  lsection  lexperiencing  lroad  lunevenness  lwith  lan  lIRI  lindex  lof  l7.70  lm  l/  lkm  land  lthe  lSDI  lvalue  lof  lthis  lroad  lsection  lat  l67.20  lwith  lmoderate  ldamage  lconditions.  lSDI  lhas  la  lpositive  leffect  lon  lIRI.  lCorrelation  lof  lIRI  lvalue  lof  leach  lvehicle  lto  lSDI  lvalue  lhas  la  lvery  lstrong,  lsignificant  land  lunidirectional  lrelationship.  lThe  lsurvey  lvehicle  lrecommended  las  la  lmedia  lsurvey  lis  lthe  l113cc  lMio  lGT  lvehicle.  lAppropriate  ltreatment  lfor  lthe  lPakah  l-  lPucangan  l-  lGesikharjo  lroad  lsection  lis  lroutine  lmaintenance  lwith  la  lplanned  lbudget  lof  lRp.  l24,124,000.00. Keywords  l:  lIRI,  lSDI,  lRoad  lFunctional  lConditions,  lCost  lBudget  lPlan  l(RAB)